Wide range applications of botulinum toxin in medicine - literature review - Serwik-Trandasir, Aleksandra; Kania, Agata; Gonet, Malwina; Miszczyk, Karolina; Włodarczyk-Cybulska, Karolina; Maj, Patrycja; Sergiel, Natalia; Mozer, Piotr; Maternia, Jakub; Lazar, Michal (Journal of Education, Health and Sport, 2023)
Introduction and purpose : Botulinum toxin is one of the most dangerous natural toxins. Botulinum toxin poisoning causes botulism. Botulism is a set of systemic symptoms resulting from flaccid muscle paralysis. The first symptomatology of toxin poisoning was described at the beginning of the 19th century. After more than 200 years, botulinum toxin is associated primarily with aesthetic medicine treatments, where it is used to temporarily improve the appearance, mainly by reducing mimic wrinkles. Aim of the study: The aim of the study is to collect information available in PubMed, Google Scholar, academic textbooks and characteristics of botulinum toxin medicinal products, especially regarding its wide use, mechanism of action, adverse events and contraindications. As a result, the presentation of the versatile use of botulinum toxin as a medicinal product in many fields of medicine. Brief description of the state of knowledge: Botulinum toxin is produced by the anaerobic bacteria Clostridium botulinum. Its mechanism of action consists in flaccid muscle paralysis. Most preparations with botulinum toxin are only registered for strictly defined aesthetic medicine treatments. Other registered indications for the use of medicinal products with botulinum toxin include overactive bladder, various types of spasticity and prevention of headaches. In addition, in medicine, botulinum toxin is commonly used off-label. Summary: Botulinum toxin is widely used not only in aesthetic medicine. Intramuscular injections of botulinum toxin are successfully used in various fields of medicine, such as: urology, neurology, ophthalmology, gastroenterology, dermatology, gynecology, otolaryngology, dentistry and even psychiatry.